2020
DOI: 10.2147/dhps.s237021
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rational Drug-Use Evaluation Based on World Health Organization Core Drug-Use Indicators in a Tertiary Referral Hospital, Northeast Ethiopia: A Cross-Sectional Study</p>

Abstract: Background: Irrational use of drugs is often observed in health-care systems throughout the world, particularly in developing countries. The World Health Organization estimates that more than half of all medicines are prescribed, dispensed, or sold inappropriately and that half of all patients fail to take them correctly. Therefore, the study was aimed at investigating the practice of rational drug use in a referral and teaching hospital in Northeast Ethiopia. Methods: A hospital-based cross-sectional design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 4 publications
4
25
2
Order By: Relevance
“…Moreover, the value was also higher than the findings from South Ethiopia (1.9) [ 12 ], North Ethiopia (1.96) [ 17 ], East Ethiopia (1.9) [ 28 ], and West Shoa zone (1.74) [ 29 ]. However, this was in line with the value reported from Nekemte helth center (2.1) [ 16 ] and less than that of a study conducted in North East Ethiopia (2.5) [ 30 ], North West Ethiopia (2.4) [ 13 , 15 ], and public hospital of Eastern Ethiopia (2.34) [ 31 ]. Lower findings were also reported from Sierra Leone (4.37) [ 32 ], Kenya (2.9) [ 11 ], Pakistan (3.4) [ 33 ], Zambia (2.4) [ 10 ], and Egypt (2.5) [ 34 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the value was also higher than the findings from South Ethiopia (1.9) [ 12 ], North Ethiopia (1.96) [ 17 ], East Ethiopia (1.9) [ 28 ], and West Shoa zone (1.74) [ 29 ]. However, this was in line with the value reported from Nekemte helth center (2.1) [ 16 ] and less than that of a study conducted in North East Ethiopia (2.5) [ 30 ], North West Ethiopia (2.4) [ 13 , 15 ], and public hospital of Eastern Ethiopia (2.34) [ 31 ]. Lower findings were also reported from Sierra Leone (4.37) [ 32 ], Kenya (2.9) [ 11 ], Pakistan (3.4) [ 33 ], Zambia (2.4) [ 10 ], and Egypt (2.5) [ 34 ].…”
Section: Discussionsupporting
confidence: 81%
“…The percentage of encounters with antibiotics was 44% which was higher than the WHO standard value of 20.0—26.8% [ 5 , 26 ]. It was higher than the antibiotics utilization in East Ethiopia (37.5%) [ 28 ] and North East Ethiopia (34.64%) [ 30 ]. But, it was lower than reports from Nekemte health center (69.1%) [ 16 ], South Ethiopia (58.1%) [ 12 ], North Ethiopia (58.6%) [ 20 ], West Shoa zone (48.9%) [ 29 ] and North West Ethiopia (71.36%) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also relatively lower than the review performed at primary health care centers in the WHO Africa region, which reported a 25% injection use rate [ 6 ]. In comparison, this result was relatively less than the findings of the review in Ethiopia with an injection average of 18.3% [ 12 ]. This difference may be associated with the fact that this review included articles conducted after 2015, while the other review included all studies conducted since the beginning of the 1990s, and during this period injection dosage form was relatively the most widely used in Ethiopia [ 21 ].…”
Section: Discussionmentioning
confidence: 64%
“…The data were exported to OpenMeta Analyst software and the heterogeneity across the articles was assessed by determining the I 2 statistics using Der Simonian and Laird’s random-effects model at a 95% confidence level. The prescribing indicators used in this review to measure drug use patterns in health care facilities include; Average number of medicines per encounter; Percentage of antibiotic prescriptions; Percentage of injection prescriptions; Percentage of generic drugs prescribed; and Percentage of prescribed drugs from the essential drug list [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] Drug utilization is defined as “the marketing, distribution, prescription and use of drugs on society with special emphasis on the resulting medical and social consequences.” [ 13 ] Drug utilization studies empower rational therapeutics in identification of errors in implementing therapy and find appropriate remedies and solutions to rectify them. Rational drug prescribing is defined as “the use of the least number of drugs to obtain the best possible effect in the shortest period and at a reasonable cost.”[ 14 15 16 ] Prescription monitoring and drug utilization studies focus on determining the causes and associated problems and also offer actionable feedback to the prescriber so as to increase their perceptions and familiarize them about the irrationality in their use of drugs. [ 17 18 19 ] These studies ascertain and evaluate the efficacy, safety, convenience, and economic aspects of the use of drugs all levels in the chain of use of drugs.…”
Section: Introductionmentioning
confidence: 99%